The incorporation of thinking skills in the school curriculum - Mahyuddin, Rahil; Lope Pihie, Zaidatol Akmaliah; Elias, Habibah; Konting, Mohd Majid (Penerbit Universiti Sains Malaysia, 2004)
The focus of current classroom teaching in Malaysia is the utilization of metacognitive strategies especially thinking skills. In fact many educational psychologists argued that thinking skills are important aspects in education (Sternberg, 1990a, l990b). In Malaysia, it is realized that many teachers are not fully capable of incorporating thinking skills in their teaching strategies. Therefore it is the objectives of this study to find out how far students are inculcated with: a) critical thinking; b) creative thinking; and c) divergent/convergent thinking. A research survey was carried out on 387 secondary school students aged between 15–16 years. Results showed that teachers incorporated critical thinking skills, creative thinking skills as well as convergent/divergent thinking skills in their teaching of their subjects. Though this study showed that there is a new trend in teaching and learning where students are actively involved in the learning process, there is plenty of room for improvement in incorporating the thinking skills. The implications of this study on education and teacher training are discussed in this paper.